Design of Formative-Summative Evaluation Model Based on Tri Pramana-Weighted Product - I Putu Wisna Ariawan; Wayan Sugandini; I Made Ardana; I Made Suwastika Dharma Arta; Dewa Gede Hendra Divayana (Ital Publication, 2022)
Quality in the implementation of e-learning in health universities can be measured both during the learning process and after the learning ends. Measurement can be performed through evaluation activities. The evaluation model needed was an innovative evaluation model that can look for the dominant aspects that determined the quality of e-learning implementation. One breakthrough evaluation model produced in this research to answer this need was the Formative-Summative evaluation model based on the Tri Pramana-Weighted Product. The main objective of this research was to show the quality of the Formative-Summative evaluation model design based on the Tri Pramana-Weighted Product. This research approach was based on the Borg & Gall development model, which focused on the design development stage. The subjects involved in conducting trials of the evaluation model design were 34 respondents. The technique for determining the subject was carried out using a purposive sampling technique. In addition, the tool used to conduct the trial was a questionnaire. The location for filling out the questionnaire was in health universities and colleges in the province of Bali. The technique used to analyze the data from the test results was descriptive quantitative by comparing the average percentage of the quality of the test results with the percentage of quality that refers to the five-scale categorization. The results showed that the percentage of the design quality of the Formative-Summative evaluation model based on the Tri Pramana-Weighted Productof 88.02%. This means that the quality of the evaluation model design was included in the good category. The impact of the results of this research on the field of education was to present an innovation in evaluation activities that made it easier for educational evaluators to measure the quality of e-learning, especially in health universities and colleges. Doi: 10.28991/ESJ-2022-06-06-016 Full Text: PDF